2014
DOI: 10.1080/09168451.2014.940275
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-specific antibodies to target amyloid β oligomers and their application to immunotherapy for Alzheimer’s disease

Abstract: Amyloid β-protein (Aβ) oligomers, intermediates of Aβ aggregation, cause cognitive impairment and synaptotoxicity in the pathogenesis of Alzheimer's disease (AD). Immunotherapy using anti-Aβ antibody is one of the most promising approaches for AD treatment. However, most clinical trials using conventional sequence-specific antibodies have proceeded with difficulty. This is probably due to the unintended removal of the non-pathological monomer and fibrils of Aβ as well as the pathological oligomers by these ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 146 publications
2
27
0
Order By: Relevance
“…Remarkably, the details of antibody binding seem to hinder Aβ aggregation and promote disaggregation in two ways. First, the antibody occludes half of the “hydrophobic core” sequence responsible for self-association and oligomerization5, residues Leu17 Aβ –Ala21 Aβ . Second, the hairpin turn is disrupted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the details of antibody binding seem to hinder Aβ aggregation and promote disaggregation in two ways. First, the antibody occludes half of the “hydrophobic core” sequence responsible for self-association and oligomerization5, residues Leu17 Aβ –Ala21 Aβ . Second, the hairpin turn is disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation and aggregation of Aβ peptides in brain takes many forms in addition to plaques, including soluble monomers and oligomers, and insoluble fibrils, with a large range of molecular weights from 10 to 1,000 KDa (see review ref. 5). In vitro and ex vivo evidence suggests that soluble oligomers, i.e.…”
mentioning
confidence: 99%
“…The value of AβOs as targets for immunotherapy and the status of clinical candidates have been recently reviewed [49, 124]. Although a caveat has suggested that antibodies bound to AβOs might activate microglia and potentiate AβO neurotoxicity [120], such toxicity is not in harmony with numerous reports of neuroprotection [49].…”
Section: Therapeuticsmentioning
confidence: 99%
“…Low concentrations of soluble oligomers and the lack of localized high concentrations of such small assemblies impede imaging applications. The wealth of non-overlapping, oligomer-specific monoclonal antibodies (Kayed, et al, 2010, Liu, et al, 2015, Murakami, 2014) indicates that multiple conformational states with different properties of these biologically potent assemblies exist and await ligand development.…”
Section: Probes Of Early Assembly Stages Of Misfolded Protein Patmentioning
confidence: 99%